Antibacterial effect of oregano oil and its main component carvacrol on Campylobacter jejuni isolates from broiler caecum - Elma Hrustemović; Faruk Čaklovica; Jasmina Djedjibegovic; Kenan Čaklovica; Enida Članjak-Kudra (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Campylobacter jejuni is a colonizer of the intestines of animals, but the highest prevalences were recorded in the cecum of broiler chickens. Production errors contribute to the prevalence of broiler carcasses exceeding permitted norms, which increases the incidence of consumer disease from campylobacteriosis, a foodborne disease. In order to prevent people from getting sick, many producers resort to the prophylactic use of antibiotics in broilers, but this practice leads to antibiotic resistance. The aim of the work is to outline the possibility of using oregano oil as an alternative to antibiotics in order to reduce the colonization of the cecum with Campylobacter jejuni in broiler chickens, which will contribute to the microbiological integrity of chicken meat, but also to reduce the spread of antibiotic resistance. In vitro tests show the antibacterial activity of oregano oil and its main antibacterial component carvacrol on Campylobacter jejuni isolates from the cecum of broiler chickens, and in vivo tests throughout the fattening period indicate a significant reduction in cecal colonization in the first, but not the last, days of fattening, suggesting the importance of further tests.